Analisis Investasi Kelayakan Penambahan Armada Terhadap Biaya Oprasional dan Layanan - Prayogi, Tio Isman; Muhimatul Khoiroh, Siti (Fakultas Teknik UMRI, 2025)
This study investigates the feasibility of investing in additional logistics fleets at PT XYZ, a manufacturing company based in East Java engaged in the production of rice and glutinous rice flour using imported raw materials. The complexity of distribution in the context of growing demand from MSME customers has caused operational problems in the form of late deliveries and backlog orders due to the limited number of available fleets. To overcome these problems, this study applies a quantitative approach based on investment analysis techniques, including Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Sensitivity Analysis. Primary data were obtained from field observations and interviews, while secondary data came from the company's logistics records for the period November 2023 to January 2024. The results of the analysis show that additional fleets have a significant impact on improving service quality and distribution cost efficiency. The NPV and IRR approaches indicate that the investment is financially feasible, with a positive NPV value and IRR exceeding MARR. Meanwhile, the Payback Period is within a reasonable payback period according to the economic life of the fleet. Further sensitivity analysis confirms that variables such as operating costs and annual income are the main determinants of investment feasibility. These findings provide a strategic basis for data-based logistics investment decision-making, while strengthening the company's competitiveness in meeting customer expectations amidst competitive market dynamics.